PENINGKATAN HASIL BELAJAR PESERTA DIDIK MELALUI MODEL PEMBELAJARAN PROJECT BASED LEARNING PADA MATERI BANGUN RUANG SISI DATAR PRISMA DAN LIMAS - Helda Yuniarti; Rini Setianingsih; Iswana Surawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to determine the increase in student learning outcomes through the Project Based Learning learning model on the material of flat-sided prisms and pyramids. This research was conducted at SMP Negeri 2 Pamekasan in the second semester of the 2023/2024 academic year. This research is collaborative classroom action research using the Kemmis and McTaggart model. Observation and test collection techniques were carried out in two cycles. The cycle stages consist of planning, action, observation, and reflection. Findings during carrying out learning activities in cycles I and II showed that the completeness of students' learning outcomes had increased. In the first cycle, 7 students got grades in the good category with a percentage of 21.88% and in the poor category, there were 25 students with a percentage of 78.12%. This shows that more students get a score below the KKM 70 than students who complete it. Meanwhile, in cycle II, 3 students got very good grades with a percentage of 9.38%, 15 students in the good category with a percentage of 46.88%, 10 students in the fair category with a percentage of 31.25% and the poor category as many as 4 children with a percentage of 12.5%. From the learning results of these students, it can be said that as many as 28 students have achieved completeness in classical learning outcomes, namely 87.5%. Based on completeness data, students' learning outcomes have exceeded the KKM 70 and the minimum limit for classical completeness is 85%. The results of the research show that the use of the project-based learning model on the material of flat-sided prisms and pyramids can improve mathematics learning outcomes for class VIII SMP Negeri 2 Pamekasan for the 2023/2024 academic year.